Cerebral venous thrombosis presenting like a subdural hemorrhage at magnetic resonance imaging: An Italian case report. (2018) - Di Caprera, E.; De Corato, L.; Giuricin, V.; Pensabene, M.C.; Marfia, G.; Melis, M.; Garaci, F.; Floris, R.
Abstract: Cerebral venous sinus thrombosis (CVST) is responsible for 1–2% of all strokes in adults. Venous occlusive disease is a less common condition than the arterial one, but probably underestimated in the past [1 ]. Its early detection is crucial to ensure appropriate therapy, to prevent irreversible brain injury. The neuroradiological study is crucial to formulate the diagnosis. Unenhanced computed tomography (CT) is usually the first imaging study performed on an emergency basis. We report the case of a woman who present a migrant headache, resistant to the therapy. It was at first performed an axial CT scan of the brain that was negative. Afterwards the Patient did an MRI which proves the presence of a hyperintensity rhyme, localized in the left temporal region, in the subdural space, diagnosed like a subdural hemorrhage. Considering the type and increase of headache, neurologist suggest to perform a venography PC sequence that finally demonstrate the correct diagnosis of a filling defect of left spheno-parietal sinus.